Proceedings of the 2017 CHI Conference Extended Abstracts on Human Factors in Computing Systems 2017
DOI: 10.1145/3027063.3053204
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Remote Presence Enhanced with Contactless Object Manipulation

Abstract: A telepresence robot is a mobile telecommunication device, remotely controlled by its "pilot", which supports an embodied presence of the pilot in a different location (the "local setting"). A common problem with telepresence robots is their limited capability of interacting with the physical environment. A potential solution, explored in the present study, is supporting "double remote control" interaction, that is, making it possible for the pilot, in addition to remotely controlling the robot, to also remote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A small-scale pre-study, reported in an earlier work-in-progress paper [15], was performed to test our research methodology and prototyping approach. Several changes in the method, including a revised procedure and rating scales, and the use of a different MRP system, were made as a result of the pre-study.…”
Section: Methods 31 Research Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…A small-scale pre-study, reported in an earlier work-in-progress paper [15], was performed to test our research methodology and prototyping approach. Several changes in the method, including a revised procedure and rating scales, and the use of a different MRP system, were made as a result of the pre-study.…”
Section: Methods 31 Research Methodologymentioning
confidence: 99%
“…The command was forwarded to the Wizard, who discreetly manipulated the object in question either manually (doors, blinds, and lights) or through a remote control (TV and toy car). The Wizard was pre-trained and acted in this role in the pre-study [15]. In all cases, except for opening doors, the Wizard could stay out of the robot's view by taking into account the robot's camera angle.…”
Section: Locationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Design concepts that can help more efficiently integrate humanrobot interaction into physical and social contexts (e.g., double remote interaction, [9]) will be discussed by the participants.…”
Section: Design Approachesmentioning
confidence: 99%